Silica-grafted ionic liquids for revealing the respective charging behaviors of cations and anions in supercapacitors - Qingyun Dou (Nature Portfolio, 2017)
Quantifying the individual capacitance contributions of in-pore ions during charging remains a challenge. Here the authors design silica-grafted ionic liquids to reveal the charging behaviors of cations and anions separately, providing fresh insight into the storage mechanism of supercapacitors.